Effect of dietary globin, a natural emulsifier, on the growth performance and digestive efficiency of broiler chickens. Issue 1 (2nd January 2019) - Dabbou, Sihem; Schiavone, Achille; Gai, Francesco; Martinez, Silvia; Madrid, Josefa; Hernandez, Fuensanta; Martínez Marín, Andrés L.; Soglia, Dominga; Sartore, Stefano; Kalmar, Isabelle D.; Gasco, Laura; Nery, Joana
Abstract: The feed utilisation of young chicks is characterised by a suboptimal fat digestibility, which can be improved by means of dietary emulsifiers. The objective of this study was to evaluate the effect of dietary Globin on the energy efficiency and digestibility of starter feeds and on the production performance of broilers throughout the whole rearing cycle. A total of 224-day-old ROSS 708 chickens (14 birds/pen, 8 replicates/treatment) were fed ad libitum with either a basal diet (C) or a basal diet with the addition of 0.05% Globin during the starter (d1–10), growing (d10–25) and finisher (d25–35) periods. Nutrient digestibility (aD), protein metabolisability (aMCP ), energy efficiency (EE) and net energy for production (NEp) were assessed during the starter period. The average daily feed intake (ADFI), average daily gain (ADG), feed conversion ratio (FCR) and protein efficiency ratio (PER) were measured of each growth period. Globin significantly decreased FCR ( p = .020) and increased aDfat ( p = .021), EE ( p = .028) and NEp ( p = .011) during the starter period. aMCP ( p = .049) and PER ( p = .039) were higher in the Globin group than in the Control group. The increased availability of energy from dietary fat, as a result of Globin supplementation, possibly shifted the use of the absorbed amino acids towards an anabolic metabolism, and this could explain the increased aMCP and PER but similar aDCP . The overall performance was similar between groups, although Globin tended to increase PER ( p = .064) overall. Highlights: Globin dietary supplementation was studied in broiler chickens. Globin improved digestibility and nutrient efficiency utilization in the first period. The overall performance was similar between groups.